2013
DOI: 10.1155/2013/276984
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Followup of LaserIn SituKeratomileusis for Hyperopia Using a 213 nm Wavelength Solid-State Laser

Abstract: Purpose. To evaluate the long-term efficacy, accuracy, stability, and safety of hyperopic laser in situ keratomileusis (LASIK) using a 213 nm wavelength solid-state laser. Methods. This prospective noncomparative case series consisted of 34 eyes of 17 patients which underwent hyperopic LASIK using a 213 nm solid-state laser (Pulzar Z1, CustomVis) at an outpatient refractive surgery center in Manila, Philippines. The preoperative and postoperative examinations included uncorrected distance visual acuity (UDVA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…The spherical equivalent (SE) predictability outcomes obtained in this investigation were similar to previous studies. 6,18–20 The spherical equivalent stability shows a change of more than 0.50 D in 33% of cases between 3 and 36 months after surgery and in 22% between 12 and 36 months after surgery; these results are in concordance with those of previous studies. 6 These outcomes could be influenced by the increase of the hyperopia related to the changes in accommodation with age.…”
Section: Discussionsupporting
confidence: 89%
“…The spherical equivalent (SE) predictability outcomes obtained in this investigation were similar to previous studies. 6,18–20 The spherical equivalent stability shows a change of more than 0.50 D in 33% of cases between 3 and 36 months after surgery and in 22% between 12 and 36 months after surgery; these results are in concordance with those of previous studies. 6 These outcomes could be influenced by the increase of the hyperopia related to the changes in accommodation with age.…”
Section: Discussionsupporting
confidence: 89%
“…Adjunctive use of Mitomycin C with PRK after primary LASIK has been shown to be effective and safe using 193 nm excimer lasers. With the development and growing use of the 213 nm solid-state laser, published studies [ 12 14 ] have suggested that despite the known differences in their ablation characteristics, clinical results in efficacy and safety have been comparable. In a study by Sanders et al, the authors showed that cellular responses after irradiation with 213 nm compared with 193 nm wavelengths are consistent with good clinical outcomes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…We plan to report the outcomes over a longer period, because some studies found average increase in hyperopia +0,54 over 5 years postoperatively, which is more than expected physiologically and can be indicator of destabilization of cornea after LASIK (20).…”
Section: Discussionmentioning
confidence: 99%